EFFECT OF INHALED HEPARIN ON METHACHOLINE-INDUCED BRONCHIAL HYPERREACTIVITY - (:unkn) unknown (AMER COLL CHEST PHYSICIANS, 1995)
Although heparin is used as an anticoagulant, its biologic function has remained unclear since the 1920s. Glycosaminoglycan heparin possesses multiple noncoagulant properties, including anti-inflammatory actions, and it is possible that heparin may inhibit airway hyperreactivity. Thus, the purpose of the present investigation was to study the effect of inhaled heparin on methacholine-induced bronchoconstriction, Thirteen subjects (7 women, 6 men) with mild asthma were included in the study. Bronchial provocation tests were performed in a single-blind, crossover, randomized order and repeated 45 min after placebo or aerosolized heparin inhalation (1,000 U/kg), The heparin inhibited bronchoconstriction induced by methacholine. In the methacholine challenge test, heparin treatment resulted in an increase in the mean PD20 over placebo: 5.26 +/- 4.80 mg/mL vs 10.57 +/- 5.72 mg/mL (p<0.0002). These data suggest that inhaled heparin may have an inhibitory role on methacholine bronchial challenge, possibly via a direct effect on smooth muscle.
Keywords: BRONCHIAL HYPERREACTIVITY; INHALED HEPARIN; METHACHOLINE; AIRWAY SMOOTH-MUSCLE; MAST-CELL GRANULES; CALCIUM RELEASE; INHIBITION; ASTHMA; GLYCOSAMINOGLYCANS; REACTIVITY; RESPONSES; BINDING; ANTIGEN